AN ATYPICAL CASE OF BILATERAL CORNEAL OPACITY: WHAT ARE THE POSSIBLE DIAGNOSIS? - Zarwan, Jessica; Siregar, Astrid Mariam Khairani; Pintary, Marsha Rayfa; Widyawati, Syska; Martha, Faraby; Rhendy, Rio (Majalah Oftalmologi Indonesia, 2024)
Introduction: Corneal opacity can be divided into inflammatory and noninflammatory entities. The clinical presentation and characteristics of a corneal opacity can often help reach a diagnosis. However, atypical cases are more challenging to diagnose. This report aims to explore an atypical case of corneal opacity and the diagnostic approach through its clinical presentation. Case Report: A thirty-seven-year-old female patient had a chief complaint of gradual blurry vision in both eyes and slowly growing whitish lesions one year prior. The patient recalled a history of bilateral eye redness two years ago. The anterior segment examination and AS-OCT revealed bilateral, smooth, oedematous pearly-white elevated opacity with well-demarcated margins at the center of the cornea, with epithelial depth. The diagnosis of corneal keloid was favored, with GDLD and SND as the differential diagnosis. In local anesthesia, the patient underwent superficial keratectomy and amniotic membrane transplantation of the right eye. On one month follow-up, the patient felt an improvement in her subjective complaints with a normal appearance of the cornea. Discussion: The atypical characteristics found in our case didn’t fit a single mold, as it shared features of post- injury hypertrophic scar, degenerative, and dystrophy. We diagnosed the patient with corneal keloid caused by suspicion of subclinical infection. Although GDLD and SND were still possible, the working diagnosis was enough to warrant a therapeutic surgical removal. Conclusion: Atypical presentations make diagnosis more challenging. However, despite improvements in diagnostic modalities, signs, and symptoms remain very helpful in reaching a working diagnosis.